Pengaruh Heart Rate Variability terhadap Kesintasan Pasien dengan Kanker: Laporan Kasus Berbasis Bukti - Kosasih, Kartika Anastasia; Raniah, Nida; Putranto, Rudi; Rajabto, Wulyo; Shatri, Hamzah; Faisal, Edward; Poespitasari, Vinandya Irvianita (Jurnal Penyakit Dalam Indonesia, 2025)
Depression, anxiety, and poor outcomes in cancer are possibly mediated by autonomic dysfunction. Autonomic disfunction found in cancer patients can cause increase in sympathetic tone and decrease in cardiac muscle vagal tone. Heart rate variability (HRV) is a non-invasive index for measuring vagal response and a potential stress response in autonomic dysfunction. In patients with cancer, high vagal tone measured by HRV is significantly correlated with increased overall survival. This evidence-based case report aims to investigate the role of HRV as a prognostic factor in cancer patients. Literature search was done by two authors on five databases: Pubmed, Cochrane Library, EMBASE, ProQuest dan MEDLINE (EbscoHost) in accordance with clinical question. Articles were selected using inclusion and exclusion criteria, then critical review was performed. Quality of the studies was evaluated using the Center of Evidence-Based Medicine, University of Oxford guideline. Two systematic review and four cohort study was included. Increased HRV index is consistently correlated with increased overall survival (OS) in cancer patients. One meta-analysis study found that OS is significantly longer in group with higher HRV (Hazard ratio, HR = 0.70, IK95% 0.60 – 0.82, p < 0.001, I2 = 27%). In conclusion, HRV can be used as a prognostic factor in advanced stage cancer patients. Increased HRV is associated with better OS.